Surviving ISIS:Life Stories of Yezidi Women - Rizkalla, Marian Mounir (AUC Knowledge Fountain, 2019)
My research centers on the experiences of five Yezidi female refugees in Kurdistan and how they survived the ISIS siege of their hometown- Sinjar. Yezidis, an ethno-religious community living in northern Iraq were the center of most news stories for the massacres they faced under ISIS and the sex-enslavement of thousands of them. This research attempts to show how a large-scale event like genocide impacts the life of the individual on the micro-level, but also how individual narratives are instrumental in constructing a collective identity, presenting Yezidis as a historically persecuted group. By examining sectarian relations in Iraq before and after the American invasion of 2003, the research situates the Yezidi genocide within the context of sectarian politics in the nation-state. Personal narratives are used as the main methodology to portray how each woman uniquely experienced and remembers the fall of Sinjar, the survival phase and how she lives as a refugee in the aftermath. The impact that trauma has on memory is an important element of the personal narratives but also speak of the collective Yezidi experience.